Genomic Analyses for Selective Signatures and Genes Involved in Hot Adaptation Among Indigenous Chickens From Different Tropical Climate Regions - Xu, Nai-Yi; Liu, Zhen-Yu; Yang, Qi-Meng; Bian, Pei-Pei; Li, Ming; Zhao, Xin (Frontiers in Genetics, 2022)
Climate change, especially weather extremes like extreme cold or extreme hot, is a major challenge for global livestock. One of the animal breeding goals for sustainable livestock production should be to breed animals with excellent climate adaptability. Indigenous livestock and poultry are well adapted to local climate and they are good resources to study the genetic footprints and mechanism of the resilience to weather extremes. In order to identify selection signatures and genes that might be involved in hot adaptation in indigenous chickens from different tropical climates, we conducted a genomic analysis for 65 indigenous chickens which inhabit in different climates. Several important unique positively selected genes (PSGs) were identified for each local chicken group by the XP-EHH. These PSGs, verified by CLR, Fst, π, Tajima's D and DCMS, are related to nerve regulation, vascular function, immune function, lipid metabolism, kidney development and function, which are involved in thermoregulate and hot adaptation. However, one common PSG was detected for all three tropical groups of chickens by XP-EHH but was not confirmed by other four types of selective sweep analyses. These results suggest that hot adaptability of indigenous chickens from different tropical climate regions has been evolved in parallel by taking different pathways with different sets of genes. The results from our study have provided reasonable explanation and insights for the rapid adaptation of chickens to diverse tropical climate and offered practical values for poultry breeding.